The fragility of Faroese jazz - Ludvig, Arnold, 1968- (2019)
In this essay, I share my research on the history of Jazz in the Faroe Islands. This research includes participant observation and interviews with interlocutors. This essay concludes with a description of my current artistic practice and how it is inextricably linked to the Faroese jazz scene. It is my hope that this essay will stimulate a discussion amongst musicians, composers, historians, journalists, and audience members about the evolution and development of jazz in the Faroe Islands.